Núcleo logístico empresarial Sabana Centro 2040: Plan parcial Parque Industrial Agrozipa (2017)
This project is developed in Zipaquirá (Cundinamarca) is analyzed from different aspects and dynamics of city-region of the province savannah center, besides its area of influence at the national and international level from agro- industrial vocation, as one of the main uses of the territory, it is now a village in a participatory and integrated development in their strategies. After exhaustive studies made in the municipality sets the various weaknesses, threats, opportunities and strengths, corresponding to this is identified issues such as migration overwhelmed to Bogotá therefore design proposals for the improvement and empowerment of the place, generating a partial plan with a polygon of 12 hectares, with your approach is for the evolution and competition of the municipality with respect to the region, these are divided by different axes and structural systems as the logistical, administrative, commercial, industrial and recreational activities where they are complemented with the mobility systems, environmental and socio-economic, meaning a growth in the projection to the objective of globalization.